Effects of indoor plants on office workers: a field study in multiple Dutch organizations - de Vries, Sjerp; Hermans, Tia; Langers, Fransje (Frontiers in Psychology, 2023)
In the period 2019–2020, the effect of plants in the workspace on (a) the physical indoor climate, (b) the perception of the workspace by office workers, and (c) their health, well-being and functioning was investigated in nine organizations. This paper reports the outcomes of the latter part. A conceptual model describing the short-term, medium and long-term effect of plants on people was formulated, containing 18 outcome variables. A “Before After Control Impact” quasi-experimental research design was used. A control workspace and an intervention workspace were selected in each of the organizations. A pre-measurement was conducted in both. Correlational analyses, based on the pre-measurements in all organizations and workspaces, confirmed the associations proposed by the conceptual model to a large extent. After placing plants in the intervention workspace, a maximum of two post-intervention measurements were conducted (due to COVID-19 not in all nine organizations), the last one at least 4 months after the introduction of the plants. Overall significant effects were found on complaints about dry air (fewer), the sense of privacy (higher), the attractiveness of the workspace (higher), satisfaction with the workspace (greater) and having a health-related complaint, especially when at work (fewer). The first three effects were already observed in the analyses only including the first post-measurement. The latter two effects only showed up in the analyses including two post-measurements. No direct effect of the plants could be demonstrated on the 13 other outcome variables. The observed effects mainly concern outcome variables that are positioned at the beginning of the proposed causal chain, starting with plants and ending with mental health, absenteeism and job satisfaction.